State-dependent stock liquidity premium: The case of the Warsaw stock exchange - Szymon Stereńczak (International Journal of Financial Studies, 2020)
The effect of stock liquidity on stock returns is well documented in the developed capital markets, while similar studies on emerging markets are still scarce and their results ambiguous. This paper aims to analyze the state-dependent variance of liquidity premium in the Polish stock market. The Polish capital market may serve as a benchmark for other emerging markets in the region of Central and Eastern Europe, hence the results of this research should be of great interest for investors and policy makers in Poland and other post-communist European countries. In the empirical, study a unique empirical methodology has been applied, which guarantees the uniqueness of the results obtained. The results obtained suggest that on the Polish stock market exists stock liquidity premium, which is statistically significant, but constitutes only a small fraction of returns. It also does not increase during periods of bearish market, what results from the lengthening of average holding period when market liquidity decreases.
Keywords: G11; G12; 330; amortized liquidity costs; liquidity costs; liquidity premium; pricing of liquidity; Warsaw Stock Exchange